Epidemiology of cervical dysplasia - Campos Rey de Castro, Jorge (2015)
To study the epidemiology of a disease means that we must first applicant individually; in other words we need a concept as fully as possible of its fundamental features to diagnose, individualize and differentiate it from other similar processes.